Iran's Nuclear Program Discourse as Deterrence Effort against The United States of America - Rio Sundari (Journal of Diplomacy and International Studies, 2018)
The purpose of thisresearch "Iran's Nuclear Program DiscourseAs Deterrence EffortsAgainst The United States" is to explain the controversial discourse of Iran's nuclearprogram which is still being a discourse in international security politics.U.S perception toIran is always negative, this is because the relations built by these countries alwaysexperiencing obstacles. This articles use of qualitative methods with descriptive as atechnic of the research. As for the concept that the writer uses in the slice of this problem isdeterrence concept withRealist approach. For Realists view, convincing the safety of a statein an anarchic international system is the most important factor above all else. Economicsector and others can be protected if the country's security is guaranteed. Therefore, as therational actor, Iran see its nuclear programmore important as an effort to ensure the safetyfrom all potential external threats. As a rational actor, Iran considers its nuclear programmore important as an effort to ensure its security. This paper elaborates how Iran makeschoices in determining its policy between retaining its nuclear program or even halts itsnuclear program. This paper will present a graph of “Iran chooses strategy”, it will beunderstood why Iran would prefer the policy to maintain its nuclear program.